2004
DOI: 10.1093/ajcn/80.3.604
|View full text |Cite
|
Sign up to set email alerts
|

Role of cell walls in the bioaccessibility of lipids in almond seeds

Abstract: The cell walls of almond seeds reduce lipid bioaccessibility by hindering the release of lipid available for digestion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
299
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(326 citation statements)
references
References 31 publications
18
299
1
2
Order By: Relevance
“…The failure to rupture the fibrous cell walls of nuts by mechanical, enzymatic or bacterial processes results in limited release of the cellular lipid and their consequent loss in the stool. 20 Studies documenting this phenomenon have only been conducted with almonds, but the consistency of results across nuts with respect to fat loss, suggests a similarly low bioaccessibility that may apply to these other nuts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The failure to rupture the fibrous cell walls of nuts by mechanical, enzymatic or bacterial processes results in limited release of the cellular lipid and their consequent loss in the stool. 20 Studies documenting this phenomenon have only been conducted with almonds, but the consistency of results across nuts with respect to fat loss, suggests a similarly low bioaccessibility that may apply to these other nuts.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal analyses from intervention trials testing peanuts, 16 pecans, 17 and almonds [18][19][20] document increased energy loss with nut consumption. The effect size varies markedly, as did the loads provided, hampering conclusions about the magnitude of effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fat malabsorption, documented during nut diets as increased fecal fat excretion, also can contribute to the lack of weight gain. Increased stool fat losses may be due in part to the high fiber content of nuts [23] or to incomplete digestion of their matrices because the fat of nuts is enclosed within cell membranes, which are not readily available to digestive enzymes [143], an effect that can be compounded by incomplete mastication [144]. At any rate, the satiating effect of nuts with subsequent food compensation appears to be the main reason for their lack of weight-promoting effect.…”
Section: Safety Of Nut Consumptionmentioning
confidence: 99%
“…Thus, another explanation for the findings of the present study is that the digestion of the FL fat in the endosperm is impeded by the physical encapsulation of the fat of the whole FL. Ellis et al (2004) showed that chewing of almond seeds did not disrupt cell walls sufficiently to release intracellular lipids. This phenomenon may be more marked for FL, which due to their small size to a large extent will be swallowed whole.…”
Section: Discussionmentioning
confidence: 99%